Practice of Applying Affidavits in Bankruptcy Law and Postponement of Debt Payment Obligations - Rado Fridsel Leonardus; Alexander Yovie Pratama Yudha; Tata Wijayanta (Unnes Law Journal, 2023)
Civil law regulates the means of evidence as outlined in Article 1866 of the Civil Code/Article 164 HIR/Article 284 RBg which consists of written evidence, witness evidence, allegations, confessions and oaths. The existence of an Affidavit certainly makes it easier to resolve a Civil Case, especially in cases regarding Bankruptcy and Postponement of Debt Payment Obligations. The existence of an Affidavit is one aspect that confirms that the process of proving a legal problem in Indonesia is undergoing adjustments in line with the very rapid development of law in this Era of Globalization. The application of Affidavits in Bankruptcy and PKPU legal processes is important in their development. This research uses Normative Legal Research using the method of the Statute Approach. Article 299 of Law Number 37 of 2004 concerning Bankruptcy and Postponement of Debt Payment Obligations explains that the procedural law that applies in resolving Bankruptcy cases and Postponement of Debt Payment Obligations is Civil Procedure Law. Written evidence is significant in the Bankruptcy Law and PKPU process, although the process still prioritizes simple evidence. Affidavit is a written statement by someone who is considered an expert containing an explanation of a particular event object, which is then signed and submitted as written evidence in the trial. In Indonesia, an Affidavit cannot be classified as an Authentic Deed and does not have perfect evidentiary properties, but an Affidavit can be used as ordinary documentary evidence to support other evidence and help judges decide Bankruptcy & PKPU cases efficiently in order to support a simple evidentiary process and considering the short examination time.